2015
DOI: 10.1080/15324982.2015.1030798
|View full text |Cite
|
Sign up to set email alerts
|

Functional Responses of WoodyProsopis caldeniaSeedlings to Drought and Livestock Grazing in Semiarid Rangelands of Argentina

Abstract: In the semiarid rangelands of Central Argentina overgrazing and drought alter the competitive balance between woody and herbaceous vegetation, favoring an increase in Prosopis caldenia. The objective of this study was to evaluate the effect of competition in perennial grasses and water stress on the relative growth rate (RGR) and related functional attributes of P. caldenia seedlings in sites with different grazing histories: a site exposed to long term (40 or more years) continuous grazing by cattle (grazed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Conversely, other species tolerate drought stress based on a ‘water conservative strategy’ by avoiding water loss during dry and wet periods adjusting cuticular transpiration (E c ) and stomatal closure ( Villar-Salvador et al 2004 ). However, several authors agree that the main physiological drought adaptation strategy of arid climate plants seems to be the need to maintain a high water content and cell turgor, which might have a direct effect on their subsequent growth and seed production processes ( López et al 2013 ; Villalobos and Peláez 2015 ). Nevertheless, not all plants have the same strategies to respond to periods of water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other species tolerate drought stress based on a ‘water conservative strategy’ by avoiding water loss during dry and wet periods adjusting cuticular transpiration (E c ) and stomatal closure ( Villar-Salvador et al 2004 ). However, several authors agree that the main physiological drought adaptation strategy of arid climate plants seems to be the need to maintain a high water content and cell turgor, which might have a direct effect on their subsequent growth and seed production processes ( López et al 2013 ; Villalobos and Peláez 2015 ). Nevertheless, not all plants have the same strategies to respond to periods of water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted on adult trees or seedlings of other Prosopis species inhabiting hyper arid deserts, such as P. caldenia, P. glandulosa, P. flexuosa and P. pallida (Ansley et al 2007, Guevara et al 2010, de Villalobos & Peláez 2015, Salazar et al 2019) have revealed a significant capacity for phenotypic adjustment through plastic responses of biomass allocation in response to water availability in mesquites. The results here presented suggest that besides phenotypic plasticity, potentially genetically determined functional differences among populations may be very important for survival during the very crucial stages of germination and seedling emergence, perhaps before plastic responses can come into play.…”
Section: Discussionmentioning
confidence: 99%
“…across semiarid regions of Argentina and Sudan ( Campos et al, 2011 ; Morandini, Giamminola & Viana, 2013 ; Yoda et al, 2015 ). High Prosopis caldenia Burkart seed mortality has also been related to soil water availability reduction across semiarid rangelands of Central Argentina ( De Villalobos, Peláez & Elia, 2005 ; De Villalobos & Peláez, 2015 ; Risio et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%